Analisis Kualitas Pelayanan Kesehatan terhadap Kepuasan Peserta JKN di Puskesmas Bandaharjo Semarang - Widyaningrum, Amanda Monica; Nurvita, Silvia (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Puskesmas is a Health Technical Implementation Unit (UPT) under the supervision of the District/City Health Service. In general, community health centers must provide health services that carry out public health efforts and first-level individual health efforts, prioritizing promotive and preventive efforts to achieve the highest level of public health in their work area. The quality of health services is part of the indicators of participant satisfaction, both in terms of infrastructure, service processes, and improvements that will be received by health service users. To measure consumer satisfaction, it is important to compare the quality of services received with what they expected. This study aims to analyze whether or not there is an influence of the variables reliability, responsiveness, assurance, empathy and tangible on service quality on patient satisfaction of BPJS participants at the Bandaharjo Health Center and to determine the quality of health services at the Bandaharjo Health Center based on information from BPJS participant patients as consumers. The research was conducted in June 2024 with the research location at the Bandaharjo Health Center, Semarang City. The number of samples in this study was 71 who met the research inclusion criteria. This type of research is quantitative research, survey research method using an explanatory approach. Data analysis was carried out using Bivariate tests using the SPSS 26 chi square test. The results of the research showed that there was a relationship between the quality of health services and patient satisfaction of JKN participants between the Tangible Sig dimensions. (2-tailed) 0.034, Reliability dimension Sig. (2-tailed) 0.000, Responsiveness dimension Sig. (2-tailed) 0.034, Empathy dimension Sig. (2-tailed) 0.002, while the quality of health services in the Assurance dimension shows no relationship with patient satisfaction with Sig. (2-tailed) 0.259>0.05. It is hoped that it can provide positive input for the development of community knowledge, medical nursing personnel, as an appeal to the city government to always give special attention to health workers, especially at the Bandarharjo Semarang Health Center Health Facilities, to further improve the quality of service so that patient satisfaction can also increase, in order to maximize patient confidence in utilizing health services  Keywords: Quality of Health Services, Patient Satisfaction, JKN Participants    ABSTRAK Puskesmas merupakan Unit Pelaksana Teknis (UPT) Kesehatan dibawah supervise Dinas Kesehatan Kabupaten/Kota. Secara umum puskesmas harus memberikan pelayanan kesehatan yang menyelenggarakan upaya kesehatan masyarakat dan upaya kesehatan perseorangan tingkat pertama, dengan lebih mengutamakan upaya promotif dan preventif untuk mencapai derajat kesehatan masyakat yang setinggi-tingginya diwilayah kerjanya. Kualitas pelayanan kesehatan menjadi bagian dari indikator kepuasan peserta baik secara sarana prasarana, proses pelayanan, dan perbaikan yang akan diterima oleh pengguna layanan kesehatan tersebut, untuk mengukur kepuasan konsumen, penting untuk membandingkan kualitas layanan yang diterima dengan yang diharapkannya. Penelitian ini bertujuan untuk menganalisis ada atau tidaknya pengaruh variabel reability, responsiveness, assurance, empathy dan tangiblepada kualitas pelayanan terhadap kepuasan pasien peserta BPJS di Puskesmas Bandaharjo dan mengetahui kualitas pelayanan kesehatan di Puskesmas Bandaharjo berdasarkan informasi dari pasien peserta BPJS selaku konsumen.Penelitian dilakukan pada bulan Juni Tahun 2024 dengan lokasi penelitian di Puskesmas Bandaharjo Kota Semarang. Jumlah sampel pada penelitian ini adalah 71 yang telah memenuhi kriteria inklusi penelitian. Jenis penelitian ini adalah penelitian kuantitatif, metode penelitian survei dengan menggunakan pendekatan explanatory. Analisis data dilakukan dengan menggunakan uji Bivariat menggunakan uji chi square SPSS 26. Hasil penelitian menunjukkan ada hubungan kualitas pelayanan Kesehatan dengan kepuasan pasien peserta JKN antara dimensi Tangible Sig. (2-tailed) 0,034, dimensi Reliability Sig. (2-tailed) 0,000, dimensi Responsiveness Sig. (2-tailed) 0,034, dimensi Empathy Sig. (2-tailed) 0,002, sedangkan kulitas pelayanan Kesehatan pada dimensi Assurance menunjukkan tidak ada hubungan dengan kepuasan pasien dengan Sig. (2-tailed) 0,259>0,05. Diharapkan dapat memberikan masukan positif untuk pengembangan ilmu masyarakat, tenaga medis keperawatan, sebagai himbauan kepada pemerintah kota untuk selalu memberikan perhatian khusus bagi para petugas kesehatan terkhusus pada Fasilitas Kesehatan Puskesmas Bandarharjo Semarang dapat meningkatkan lagi kualitas pelayanan sehingga kepuasan pasien juga dapat meningkat, agar dapat memaksimalkan kepercayaan pasien dalam memanfaatkan pelayanan Kesehatan Kata Kunci: Kualitas Pelayanan Kesehatan, Kepuasan Pasien, Peserta JKN